2017
DOI: 10.4103/ija.ija_93_17
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of haemodynamic responses between clinical assessment-guided tracheal intubation and neuromuscular block monitoring-guided tracheal intubation: A prospective, randomised study

Abstract: Background and Aims:Haemodynamic responses to laryngoscopy and endotracheal intubation and their hazards are well documented. The purpose of the study was to compare the effects of laryngoscopy and intubation on cardiovascular responses when the appropriate moment for intubation was directed by either clinical judgment or train-of-four assessment.Methods:A total of 68 patients, posted for laparoscopic cholecystectomy, were randomised into two groups. In Group M patients, the trachea was intubated after train o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Unexpected intraoperative vocal fold movement and coughing could occur due to the inconsistency between the degree of relaxation of laryngeal muscles and the response of peripheral muscles to TOF under neuromuscular block monitoring 9–12 . In this situation, hemodynamic instability or unintended trauma could occur 13–15 . Therefore, the secondary outcome was defined as the incidence of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpected intraoperative vocal fold movement and coughing could occur due to the inconsistency between the degree of relaxation of laryngeal muscles and the response of peripheral muscles to TOF under neuromuscular block monitoring 9–12 . In this situation, hemodynamic instability or unintended trauma could occur 13–15 . Therefore, the secondary outcome was defined as the incidence of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, laryngeal muscles are recovered more quickly from muscle relaxation than peripheral muscles, and they can move even when there is no movement in the adductor pollicis muscle 7–12 . Moreover, unexpected intraoperative coughing and vocal fold movement can cause hemodynamic instability or unintended trauma during endolaryngeal surgery 13–15 . Previous reports have demonstrated that deep NMB could provide better surgical conditions than moderate NMB during laparoscopic surgery, such as cholecystectomy, hysterectomy, prostatectomy, and laparoscopic bariatric surgery 16–23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of complete neuromuscular blockade during intubation has also been associated with increased tachycardia and hypertension. Nandi and colleagues noted that intubation conditions were worse and there was more tachycardia and hypertension during intubation when intubation proceeded according to clinical impression of adequate relaxation rather than by verifying the presence of neuromuscular blockade with a nerve stimulator [11]. This increased heart rate and blood pressure may have resulted from the increased force required during laryngoscopy to expose the larynx when neuromuscular blockade had not been fully established yet.…”
Section: First Direct Laryngoscopymentioning
confidence: 99%
“…Nandi et al [10] concluded that using NMB monitoring offer more satisfactory intubating conditions comparing to clinical judgement as well as attenuated hemodynamic response to laryngoscopy and intubation. Study of Witkowska et al [11] showed that more time was required for intubation when NMB monitoring is used, but with better intubation conditions and minimal cardiovascular response.…”
Section: Introductionmentioning
confidence: 99%